Rape in J. M. Coetzee’s Fiction: Disgrace, Diary of a bad year and Elizabeth Costello - Petersen, Mariana Chaves (2017)
Rape is a recurrent motive in J. M. Coetzee’s fiction, it being present in novels such as Disgrace (1999), Diary of a bad year (2007) and Elizabeth Costello (2003). This work’s objective is to analyze each representation of rape in those novels to discuss the views on violence and disgrace presented. I also relate them to Coetzee’s own views such as his vison of what – despite his denial of censorship – might better remain unsaid. In Disgrace, David Lurie sees himself as falling into disgrace after he is charged by the student with whom he had an abrupt affair. Later, his daughter, Lucy, is brutally raped and chooses to keep it as a private affair. She ends up questioning male sexuality as a whole. In Diary of a bad year, Anya believes dishonor to fall over those who raped her, and not over her. However, Señor C disagrees, seeing dishonor as miasma. Finally, in Elizabeth Costello, the protagonist remembers an experience with evil she passed through with a man. She then defends that some things should not be read or written and discusses the risk that writers go through by exploring darker areas of human experience, a view which echoes Coetzee’s own.